Sustainably managing buffalo trophy quality - Robertson, Kevin, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
To be successful, wildlife utilization needs to be financially, ecologically and genetically sustainable. Regarding buffalo, trophy hunters invariably target the highest scoring, largest-horned bulls with little regard to their age or breeding status. This is a situation compounded by ill-conceived trophy scoring methods which actively encourage the hunting of pre-breeding or active breeding bulls. Over time the 'best' trophy genetics have consequently been lost and as a result trophy quality is dropping. This presentation will in detail explain the Taylor first molar teeth buffalo aging process and demonstrate how it is possible to age live buffalo bulls accurately. It will also help participants to identify breeding age bulls and those considered to be of post breeding age. The presentation will also demonstrate how to trophy score live buffalo accurately. Suggestions will also be made as to how to change public opinion as to what should constitute a 'real' buffalo trophy.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia in conjuction with the IUCN 2nd African Buffalo Symposium.